2020
DOI: 10.1177/1526924820978596
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Emergency Department Utilization and Hospital Re-Admissions in a Predominantly Obese, Racially Diverse Urban Renal Transplant Population

Abstract: Introduction: Early emergency department and hospital re-admissions are common in renal transplant recipients, but data are lacking in unique populations. Study Aim: The purpose of this study was to identify patient risk factors for multiple acute care utilization events within the first year of renal transplantation. Design: This was a single-center, retrospective cohort study of adult renal transplant recipients between 9/2013-9/2016. Patients were compared across number of emergency department visits and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…By using a multimodal approach consisting of an intraoperative nerve block and scheduled acetaminophen, Dualeh et al were able to decrease the quantity of opioids prescribed at hospital discharge. Similar results were published by Lichvar et al, who found that opioid prescriptions at discharge in kidney graft recipients was significantly lower after an opioid-sparing protocol and educational session were implemented. Other transplant centers across the US have shown comparable results after implementation of similar opioid-sparing protocols in the perioperative transplant period .…”
Section: Discussionsupporting
confidence: 89%
“…By using a multimodal approach consisting of an intraoperative nerve block and scheduled acetaminophen, Dualeh et al were able to decrease the quantity of opioids prescribed at hospital discharge. Similar results were published by Lichvar et al, who found that opioid prescriptions at discharge in kidney graft recipients was significantly lower after an opioid-sparing protocol and educational session were implemented. Other transplant centers across the US have shown comparable results after implementation of similar opioid-sparing protocols in the perioperative transplant period .…”
Section: Discussionsupporting
confidence: 89%
“…Prolonged hospital stay could lead to higher chances of contracting infections. A shorter length of stay may indicate a low-risk recipient receiving a kidney from a low-risk donor (19). EHR was also significantly associated with death-censored graft failure and mortality within the first year of kidney transplant.…”
Section: Discussionmentioning
confidence: 96%
“…Out of these, 52 full-text articles that aligned with the objective of the manuscript were reviewed. Ultimately, 17 studies were included in the final analysis, out of which twelve were cohort studies (10 retrospective, 1 prospective, and 1 ambispective) and one was a case-control study (5,(8)(9)(10)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Supplementary Figure 1 presents the PRISMA flowchart outlining the search process.…”
Section: Literature Search and Baseline Characteristicsmentioning
confidence: 99%
“…In the literature, there are several comprehensive studies evaluating hospital re-admissions and ED visits among renal transplant recipients 5 7 . However, there is limited data on the usage of the ED post-renal transplantation in Saudi Arabia and the Middle East.…”
mentioning
confidence: 99%